LOCAL WISDOM OF MANDAILING ETHNIC MARSIALAPARI IN SIPIONGOT VILLAGE, DOLOK DISTRICT, NORTH PADANG LAWAS REGENCY (International Journal of Cultural and Social Science, 2026)
Marsialapari is a tradition of mutual cooperation of the Mandailing people in agricultural activities. However, the modernization of agriculture, the use of technology, and the increase in the wage work system have affected the sustainability of this tradition in Sipiongot Village. This study aims to analyze the sustainability of Marsialapari in the midst of changes in community agriculture. The method used is descriptive qualitative research with observation, interview, and documentation techniques. The research informants consisted of community leaders, farmers, youth, and local residents. The results of the study show that Marsialapari is still carried out in agricultural and social activities, although its intensity has decreased due to changes in people's work patterns. This tradition is still maintained because it is considered a cultural identity that contains the values of mutual cooperation, solidarity, and social responsibility. The sustainability of Marsialapari depends on the role of the community and the young generation in maintaining local cultural values in the in the midst of social and agricultural changes.